Modulation of the Direction of Radiation Emitted by an InAs/GaAs Heterolaser with InAs Quantum Dots under the Influence of Acoustic Wave - Peleshchak, R.M.; Dan’kiv, O.O.; Kuzyk, O.V. (Ukrainian Journal of Physics, 2012)
A theoretical model describing the modulation of a direction of radiation emitted by an InAs/GaAs heterolaser with InAs quantum dots under the influence of an acoustic wave has been developed. The character of the dependences of the emission deviation angle on the acoustic wave frequency and the geometric sizes of quantum dots has been determined.